OP0163 2019 UPDATE OF THE JOINT EUROPEAN LEAGUE AGAINST RHEUMATISM AND EUROPEAN RENAL ASSOCIATION–EUROPEAN DIALYSIS AND TRANSPLANT ASSOCIATION (EULAR/ERA-EDTA) RECOMMENDATIONS FOR THE MANAGEMENT OF LUPUS NEPHRITIS. (2nd June 2020) - Fanouriakis, A.; Kostopoulou, M.; Cheema, K.; Anders, H. J.; Aringer, M.; Bajema, I.; Boletis, J. N.; Frangou, E.; Houssiau, F.; Hollis, J.; Karras, A.; Marchiori, F.; et al.
Abstract : Background: Up to 40% of systemic lupus erythematosus (SLE) patients develop kidney disease, which represents a major cause of morbidity. Objectives: To update the 2012 EULAR/ERA-EDTA recommendations for the management of lupus nephritis (LN). Methods: We followed the EULAR standardised operating procedures for the publication of treatment recommendations. Delphi-based methodology led to 15 questions for systematic literature review (SLR), which was undertaken by three fellows. Results: The changes include recommendations for treatment targets, use of glucocorticoids and calcineurin inhibitors (CNI), and management of end-stage-kidney-disease (ESKD). The target of therapy is complete response (proteinuria <0.5-0.7gr/24h with [near-]normal glomerular filtration rate) by 12 months, but this can be extended in patients with baseline nephrotic-range proteinuria. Hydroxychloroquine is recommended with regular ophthalmological monitoring. In active proliferative LN, initial (induction) treatment with mycophenolate mofetil (MMF 2-3g/day, or mycophenolic acid at equivalent dose) or low-dose intravenous cyclophosphamide (CY; 500mg x6 biweekly doses), both combined with glucocorticoids (pulses of intravenous methylprednisolone, then oral prednisone 0.3-0.5mg/kg/day) is recommended. MMF/CNI (especially tacrolimus) combination and high-dose CY are alternatives, for patients with nephrotic-range proteinuria and adverse prognostic factors. Subsequent long-term maintenance treatment with MMF or azathioprine should follow, with no or low-dose (<7.5 mg/day) glucocorticoids. The choice of agent depends on the initial regimen and plans for pregnancy. In non-responding disease, switch of induction regimens or rituximab are recommended. In pure membranous LN with nephrotic-range proteinuria or proteinuria >1g/24h despite renin-angiotensin-aldosterone blockade, MMF in combination with glucocorticoids is preferred. Assessment for kidney and extra-renal disease activity, and management of comorbidities is lifelong with repeat kidney biopsy in cases of incomplete response or nephritic flares. In ESKD, transplantation is the preferred kidney replacement option with immunosuppression guided by transplant protocols and/or extra-renal manifestations. Conclusion: The updated recommendations intend to inform rheumatologists, nephrologists, patients, national professional societies, hospital officials, social security agencies and regulators about the treatment of LN based on most recent evidence. Disclosure of Interests: Antonis Fanouriakis Paid instructor for: Paid instructor for Enorasis, Amgen, Speakers bureau: Paid speaker for Roche, Genesis Pharma, Mylan, Myrto Kostopoulou: None declared, Kim Cheema: None declared, Hans-Joachim Anders: None declared, Martin Aringer Consultant of: Boehringer Ingelheim, Roche, Speakers bureau: Boehringer Ingelheim, Roche, Ingeborg Bajema Consultant of: GSK, John N. Boletis Grant/research support from: GSK, Pfizer, Paid instructor for: GSK, Abbvie, UCB, Enorasis, Eleni Frangou: None declared, Frederic Houssiau Grant/research support from: UCB, Consultant of: GSK, Jane Hollis: None declared, Alexandre Karras: None declared, Francesca Marchiori: None declared, Stephen Marks: None declared, Gabriela Moroni: None declared, Marta Mosca: None declared, Ioannis Parodis: None declared, Manuel Praga: None declared, Matthias Schneider Grant/research support from: GSK, UCB, Abbvie, Consultant of: Abbvie, Alexion, Astra Zeneca, BMS, Boehringer Ingelheim, Gilead, Lilly, Sanofi, UCB, Speakers bureau: Abbvie, Astra Zeneca, BMS, Chugai, GSK, Lilly, Pfizer, Sanofi, Josef S. Smolen Grant/research support from: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Consultant of: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Vladimir Tesar: None declared, Maria Trachana: None declared, Ronald van Vollenhoven Grant/research support from: AbbVie, Amgen, Arthrogen, Bristol-Myers Squibb, GlaxoSmithKline (GSK), Janssen Research & Development, LLC, Lilly, Pfizer, Roche, and UCB, Consultant of: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, GSK, Janssen, Lilly, Medac, Merck, Novartis, Pfizer, Roche, UCB and Vertex, Speakers bureau: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, GlaxoSmithKline, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, UCB, Vertex, Alexandre Voskuyl: None declared, Y.K. Onno Teng Grant/research support from: GSK, Consultant of: GSK, Aurinia Pharmaceuticals, Novartis, Bernadette van Leeuw: None declared, George Bertsias Grant/research support from: GSK, Consultant of: Novartis, David Jayne Grant/research support from: ChemoCentryx, GSK, Roche/Genentech, Sanofi-Genzyme, Consultant of: Astra-Zeneca, ChemoCentryx, GSK, InflaRx, Takeda, Insmed, Chugai, Boehringer-Ingelheim, Dimitrios Boumpas: None declared